International and Brazilian Versions of WHOQOL-DIS: (in)adequacy to its Underpinnings - José Roberto Herrera Cantorani; Bruno Pedroso; Leandro Martinez Vargas; Claudia Tania Picinin; Luiz Alberto Pilatti; Gustavo Luis Gutierrez (Brazilian Archives of Biology and Technology, 2019)
Abstract: The present article aims to analyze the WHOQOL-DIS (World Health Organization Quality of Life - Disabilities) structure to verify this instrument’s adequacy to the theoretical principles underlying its construction. The methodology consists in an analysis of the WHOQOL-DIS underlying theory, prompting questions about the adequacies of this theoretical model. The procedure is complemented by a syntax analysis in order to verify the relevant questions for the score calculation. The obtained results show that the subjects “participation” and “autonomy” are not objectively present in the international version, although they are considered in the theories as justifying elements for the instrument’s creation. In the Brazilian version, there are questions addressed to the themes. However, these questions are also not factored into the score calculation. In conclusion, the presence of autonomy and participation in the Brazilian version of WHOQOL-DIS represents a proximity with the theoretical assumptions underlying its creation. However, because they do not compose the score calculation, this adequacy is still limited.